The Effect of Non-Saccharomyces Yeasts on Fermentation and Wine Quality - Jolly, N.P.; Augustyn, O.P.R.; Pretorius, I.S. (South African Journal of Enology and Viticulture, 2017)
Research has shown that non-Saccharomyces yeast strains can be detected throughout wine fermentation. Non-Saccharomyces yeasts can therefore influence the course of fermentation and also the character of the resultant wine. Previously it was shown that four non-Saccharomyces species, i.e. Kloeckera apiculata, Candida stellata, Candida pulcherrima and Candida colliculosa, predominated in grape must at the start of fermentation. In this study these four yeasts were used singularly and in combination with an industrial wine yeast (Saccharomyces cerevisiae strain VIN 13) to ferment must on a laboratory scale. The resultant wine was analysed for ethanol, volatile acidity, total S02 and glycerol. Results show that, in comparison with the industrial wine yeast, the non-Saccharomyces yeast strains could not ferment all the sugar. Furthermore, while the individual non-Saccharomyces-fermented wines had different chemical analyses, the wines fermented by the combinations were similar to the wine produced by the industrial yeast only. In subsequent, small-scale winemaking trials some of the wines produced by combined fermentations were judged to be of better quality than those produced by the S. cerevisiae only. However, this quality increase could not be linked to increased ester levels.